2014
DOI: 10.1080/10548408.2013.877413
|View full text |Cite
|
Sign up to set email alerts
|

A Webometric Analysis of Travel Blogs and Review Hosting: The Case of Catalonia

Abstract: Today, destination-marketing organizations and researchers are increasingly focusing their attention on travel blogs and reviews due to their potential for projecting the image of a specific destination and for influencing travel behavior and decision making. However, the criteria used to select the Web sites hosting travel blogs and reviews for study are unclear, and very few quantitative or demographic studies about users (bloggers and readers) have been conducted. The aim of this study is to propose a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Based on the webometrics of popularity, visibility and size [110], TripAdvisor is selected as the most suitable website for the case study. TripAdvisor [111] hosts almost a million reviews and opinions about the Greek region of Attica.…”
Section: Webhost Selection and Data Collectionmentioning
confidence: 99%
“…Based on the webometrics of popularity, visibility and size [110], TripAdvisor is selected as the most suitable website for the case study. TripAdvisor [111] hosts almost a million reviews and opinions about the Greek region of Attica.…”
Section: Webhost Selection and Data Collectionmentioning
confidence: 99%
“…The volume of data generated in social media has grown from terabytes to petabytes (Gandomi & Haider, 2015;He & Chen, 2014), and data stored and analysed by big companies are set to move from the petabyte to exabyte magnitude soon (Hu, Wen, Chua, & Li, 2014). Social media can be classified into blogs, review sites, media sharing, question-and-answer sites, social bookmarking, social networking, social news, and wikis (Gandomi & Haider, 2015;Marine-Roig, 2014). Lu and Stepchenkova (2015) found that the main sources for studies on UGC data are, in order of frequency: consumer review websites, blogs, media-sharing websites, social networks, and virtual communities; the main topic areas being service quality, destination image and reputation, UGC as electronic word-of-mouth (eWOM), experiences and behaviour, and mobility patterns.…”
Section: Introductionmentioning
confidence: 99%
“…situation, knowledge and skills of the user (traveller), the quantity and quality of related websites (tourist domain online), and the functionalities of the web browsers and search engines (interface) used to facilitate the results. Search engines basically consist of two parts; a parser that timelessly runs the Web and collects or updates the most significant information used to build a database indexed by key words or phrases and an online component receiving users' queries and returning corresponding results sorted by relevance and visibility [37]. These results are often presented based on the metadata of the indexed webpage, including the title, with a link and a brief summary [33].…”
Section: Otrs On Search Enginesmentioning
confidence: 99%
“…On the basis of past work and an update of the search, 12 portals are located with abundant information about Île de France during the studied period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). To choose the most suitable source, a weighted formula of aggregation of rankings [37] based on Borda's [45] positional method (B) is applied with the webometric variables visibility (V), popularity (P), and size (S):…”
Section: Data Collectionmentioning
confidence: 99%